Finite Particle Method-Based Collapse Simulation of Space Steel Frame Subjected to Earthquake Excitation - Xiao-Hong Long; Rong Yue; Yong-Tao Ma; Jian Fan (Shock and Vibration)
In the process of collapse failure of the space steel frame subjected to earthquake excitation, complex behaviors often are involved, including geometric nonlinearity, material nonlinearity, fracture, contact, and collisions. In view of the unique advantages of the finite particle method to analyze complex structural nonlinear problems, this paper utilized the finite particle method as the basic means of analysis and used MATLAB software for computational analysis. This paper first derived a finite particle method-based space steel frame model, conducted static analysis and dynamic response analysis under earthquake excitation, and compared findings with ANSYS analysis results to validate reliability. This paper established the fracture criterion and failure mode of a steel frame member. Theoretical derivation and numerical simulation indicate that the finite particle method is a feasible and effective way to simulate the collapse of space steel frame structures subjected to earthquake excitation. This method provides a new approach to study the collapse and anticollapse seismic design of space steel frame structures subjected to earthquake excitation.